A Systemic Assessment Framework for Measuring Blended Achievement in Transnational Schools as Collaborative Learning Communities - Mohamed Ziad Hamdan (Modern Perspectives in Language, Literature and Education Vol. 7, 2021)
By the beginning of the twenty-first century, education in public and private schools, as well as higher education institutions, was undergoing rapid methodological changes, shifting from huge residential to online, blended, and wireless teaching and learning. On the other hand, assessment, despite being regarded as the backbone of educational systems and the main operating mechanism of classroom educational programs, is either neglected or done irregularly, as in the case of diagnostic needs and formative assessments. Furthermore, the benefits of face-to-face communication, education, counselling, guidance, and follow-up of students’ learning successes are often lacking in online schooling (OLS). As a result, it is critical for OLS to adopt a compatible systemic approach to first deliver curricula, instruction, and learning in more rational ways; second, fill the assessment gap that current schooling is suffering from; and third, mentor students of blended learning toward their achievement goals. The systemic assessment framework presented in this study for measuring blended achievement in transnational schools as collaborative learning communities is intended to serve above ultimate reforming purposes.